2012
DOI: 10.22199/s07187475.2012.0003.00006
|View full text |Cite
|
Sign up to set email alerts
|

Validación del inventario de ansiedad y fobia social en una muestra de estudiantes universitarios mexicanos.

Abstract: RESUMENEste artículo tiene como objetivos estudiar la estructura factorial, consistencia interna, distribución, diferencias entre sexos, validez convergente y relación con la edad y deseabilidad social del Inventario de ansiedad y fobia social (Social Phobia and Anxiety Inventory [SPAI]). En una muestra de 695 estudiantes universitarios con cuotas equivalentes por sexos se aplicaron el SPAI, la Escala de ansiedad en la interacción social (Social Interaction Anxiety Scale [SIAS]), la Escala de autoverbalizacion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…Therefore, and following the recommendations of Grieve and McSwiggan [50], we wanted to include a test of social desirability in our study. The internal consistency was similar to that reported in the literature [5155]. A positive correlation was observed between the scores of the two questionnaires, which confirmed that their answers to the questions regarding moral norms were conditioned by the students, assuming a certain level of overlap.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, and following the recommendations of Grieve and McSwiggan [50], we wanted to include a test of social desirability in our study. The internal consistency was similar to that reported in the literature [5155]. A positive correlation was observed between the scores of the two questionnaires, which confirmed that their answers to the questions regarding moral norms were conditioned by the students, assuming a certain level of overlap.…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, results of the partial correlation analysis show that the association between satisfaction with life and subjective happiness is significant even when controlling for social desirability, suggesting a low shared variance between social desirability with satisfaction with life and subjective well-being. In conclusion, despite social desirability being associated with subjective well-being measures, low shared variances with them translate into participants tending to present themselves in an authentic way, with no need to show a more positive image of them than it really is when assessing their subjective well-being (Moral de la Rubia, García, & Antona, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the validation of the BIDR are presented in this section because they are not part of the central objective of the research, but correspond to a secondary analysis, that is necessary for the fulfillment of the objectives. It was obtained a reduced version (nine items) with good fit [χ 2 (26) = 38.605, p = 0.053; χ2/df = 1.485; CFI = 0.987; TLI = 0.982; RMSEA = 0.049, 95% CI (0.000, 0.090), p = 0.466; SRMR = 0.049] in a two-factor model (Self-deception and Printing Handling factors), such as that found in the Mexican population by Moral de la Rubia et al (2012). In this study, evidence of convergent validity was obtained through the average variance extracted (AVE) of the Factors ≥ 0.500 (Fornell and Larcker, 1981;Cheung and Wang, 2017) as well as the factor loadings (λ) ≥ 0.500 (Cheung and Wang, 2017); evidence of discriminant validity using the r between−factors ≤ 0.700 (Cheung and Wang, 2017) and the r 2 betweenfactors < AVE (Fornell and Larcker, 1981); evidence of discrimination by item with the corrected totalelement correlation, (r tec ) > 0.200 (Abad et al, 2011); and evidence of total internal consistency and by factors with the coefficients, α Ordinal , ω Ordinal , and GLB Ordinal > 0.700 (Trizano-Hermosilla and Alvarado, 2016; George and Mallery, 2017, see full psychometric properties of Spanish version of BIDR-9 in Appendix C).…”
Section: Balanced Inventory Of Desirable Respondingmentioning
confidence: 94%